Wampar-English Dictionary with an English-Wampar finder list - Beer, Bettina (Asia-Pacific Linguistics, 2021)
This ethnographic dictionary is the result of Hans Fischer's long-term fieldwork among the Wampar, who occupy the middle Markham Valley in Morobe Province, Papua New Guinea (PNG). Their language, Dzob Wampar, belongs to the Markham family of the Austronesian languages. Today most Wampar speak not only Wampar but also PNG's lingua franca, Tok Pisin. Six decades of Wampar research has documented the extent and speed of change in the region. Today, mining, migration and the commodification of land are accelerating the pace of change in Wampar communities, resulting in great individual differences in knowledge of the vernacular. This dictionary covers largely forgotten Wampar expressions as well as loanwords from German and Jabêm that have become part of everyday language. Most entries contain example sentences from original Wampar texts. The dictionary is complemented by an overview of ethnographic research among Wampar, a sketch of Wampar grammar, a bibliography and an English-to-Wampar finder list.